IDEAS OF LIBERAL MODERNIZATION AND "WESTERNIZATION" IN EDUCATIONAL ACTIVITIES OF R. R. AT-TAHTAWI IN EGYPT AND Y. FUKUZAWA IN JAPAN - Effendi, Bruina (The Algerian Historical Journal, 2026)
The Egyptian thinker Rifa'a Rafi' at-Tahtawi (1801-1873) and the japanese writer and philosopher Yukichi Fukuzawa (1835-1901) made a great contribution to the development of public life in their countries, contributing to the attempt to adopt the achievements of western civilization by their compatriots. Both were engaged in teaching, translating and writing, forming a prominent constellation of successful students who followed suit. Both visited western countries and were convinced of the need to borrow and adopt primarily western scientific and educational models. In their campaigns for the study of western civilization, they insisted on the importance of western knowledge, languages, and various sciences, but taking into account national peculiarities, indigenous cultures, and norms of social behavior. Therefore, both Fukuzawa and at-Tahtawi to preserve national traditions, as they were opposed to the blind tradition of the west. On the other hand, they sought to find a formula for the modernization of their societies that would allow them to preserve the sanctity and immunity of national culture, supplementing it with everything necessary for renewal and enabling an adaptation to the changing circumstances.